PM10 Source Identification: A Case of a Coastal City in Colombia - Leandro Gómez-Plata; Dayana Agudelo-Castañeda; Margarita Castillo; Elba C. Teixeira (Aerosol and Air Quality Research)
Abstract This paper assesses the spatial variation of EC, OC, major, and trace elements in an industrialized coastal city, allowing identification and tracers of PM10 emission sources. 83 samples (24 h average) were collected on quartz filters during the dry season using high-volume samplers. Major and trace elements were analyzed using ICP-AES and ICP-MS, whereas a thermal/optical carbon analyzer was used to determine OC and EC. Chemical characterization of major elements, SiO2, SO42−, MgO, and CaO, showed high spatial variation between sites. The abundance of these major elements and OC confirmed the effect of exposed land resuspension and road dust; mutually with the production of secondary organic aerosol (SOA). Trace elements showed high values of Cu, Pb, Mn, and V, indicating the influence of road traffic and some industries (Cu) and oil burning (V and Mn). Enrichment Factor analysis revealed that Mg, P, S, Cu, and Pb were highly/moderately enriched indicating the substantial contribution of anthropogenic sources. Results of diagnostic ratios and PMF receptor model of the spatially obtained data suggested major sources of PM10 as traffic-related emissions, heavy fuel oil combustion, biomass burning, and industrial processes. Back trajectory analysis (HYSPLIT) indicated air masses were coming from the North-East region of the Atlantic Ocean as the principal origin.